(untitled) (Vietnam Journal of Community Medicine, 2026)
Oropharyngeal candidiasis (OPC) remains the most common and recurrent opportunistic infection among people living with HIV/AIDS. Objective: This study aimed to evaluate the association between CD4+ T-cell counts and the prevalence of OPC in HIV-infected patients. Methods: A cross-sectional study was conducted among 52 HIV-positive outpatients at Thuan An City Medical Center, Binh Duong Province, from December 2023 to June 2024. Oral swab specimens were collected for fungal isolation and species identification. Absolute CD4+ T-lymphocyte counts were determined using flow cytometry. Results: The overall prevalence of Candida spp. was 57.7%, with Candida albicans being the predominant species (50%). Patients were stratified according to CD4+ T-cell counts into two groups: ≥300 cells/mm³ (53.8%) and <300 cells/mm³ (46.2%). Most participants (36.5%) had received antiretroviral therapy (ART) for 31–90 days. No statistically significant association was observed between overall Candida spp. infection and ART duration (p = 0.819) or CD4+ T-cell levels (p = 0.080). However, a significant association was found between C. albicans infection and patients whose CD4+ T-cell counts <300 cells/mm³ (p = 0.029). Conclusion: The risk of C. albicans infection in HIV/AIDS patients with CD4+ T-cell counts <300 cells/mm³ was 3.6 times higher than in those with CD4+ T-cell counts ≥300 cells/mm³